PELATIHAN PERHITUNGAN HPP UNTUK MENENTUKAN HARGA JUAL DAN LABA USAHA UMKM KEL.SEMOLOWARU - Annisa Kurniawan; Condro Widodo (Jurnal Pengabdian Masyarakat SENSASI, 2023)
Every business must have a selling price for each product. The selling price is obtained from production costs plus the profit desired by the business actor. However, before determining the selling price, a business actor, including Micro, Small and Medium Enterprises (MSMEs), needs to know the Cost of Goods Manufacture (COGM) of their product. The purpose of knowing the COGM in MSMEs is that MSME actors will be able to find out the costs required in the production process. However, MSMEs in Semolowaru Village still lack understanding in determining the COGM for each product. This happens due to a lack of understanding of MSME actors in determining the COGM, so that the determination of profits and selling prices of their products is also not optimal. Departing from the problems that occurred in the Semolowaru Village, a training to calculate the COGM to determine the selling price and operating profit of MSMEs in Semolowaru Village was held as a solution for MSME actors who are still having difficulties. This training method is carried out door-to-door at each MSME actor's house and is carried out through three sessions, namely: 1) material presentation session, 2) training session on calculating the cost of production, and 3) discussion session. The result of this training is that MSME actors are assisted in calculating the COGM and in determining operating profits so that they are in accordance with what is desired and are not wrong in determining the selling price of their products.